ISOLATION AND CHARACTERIZATION OF Î²-SITOSTEROL FROM ELAEAGNUS ANGUSTIFOLIA CULTIVATED IN IRAQ - AZEEZ, RAND A; S Abaas, Ibrahim; J Kadhim, Enas (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of our study was to investigate chemical constituents of leaves and seeds of Elaeagnus angustifolia since no phytochemical investigation had been done previously in Iraq. Methods: Phytochemical screening of the extracts obtained from the leaves of E. angustifolia indicated the presence of flavonoids (type of flavonols), saponins, alkaloids, steroids, and terpenoids. Thin-layer chromatography fingerprinting and the spraying reagent (concentrated H2SO4 and vanillin in ethanol) were used to identify the hexane extract containing phytosterols. Results: The different chromatographic and spectroscopic results revealed the presence of Î²â€sitosterol isolated from E. angustifolia. Conclusion: The isolation and purification afforded white crystalline powder which was subjected to chemical and spectral identification by infrared and 1H-nuclear magnetic resonance. The compound was identified as Î²â€sitosterol.